Demographic profile of patients and risk factors associated with suicidal behaviour in a South African district hospital - Aneeth Sadanand (AOSIS, 2021)
Background: Suicidal behaviour comprises self-destructive thoughts coupled with attempts at suicide, which negatively impacts the patient, family, friends, and their community. There is a paucity of data on factors influencing suicidal thoughts and behaviour in South Africa. The aim of this study was to evaluate demographic profile and risk factors associated with suicidal behaviour.